Comparisons of Quadrature Schemes with Arithmetic Mean Iterative Method for Second Kind Linear Fredholm Integral Equations - Mohana Sundaram Muthuvalu; Jumat Sulaiman (2010)
In this paper, we investigate the applications of two different quadrature schemes that is repeated trapezoidal (RT) and repeated modified trapezoidal (RMT) schemes via Arithmetic Mean iterative method to solve second kind linear Fredholm integral equations. Furthermore, the derivation and implementation of the proposed method are also included. Numerical tests and comparisons are given to illustrate the effectiveness of the proposed method.